Struktur Kata dan Suku Kata dalam Perkembangan Fonologis Bahasa Indonesia Anak Tunarungu Usia Prasekolah - Pujiastuti, Rahayu; Isani Kulup, Luluk (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
This longitudinal research aims to describe and to explain the structure of words and syllables in Indonesian phonological development of preschool children with hearing impairment. The object of this study is speech that can inform the structure of words and syllables in Indonesian phonological development of preschool children with hearing impairment. The subjects were three deaf children of group A-B TKLB which have a level of mild, moderate, and severe hearing impairment. To collect the data, the researcher used observational techniques, namely: stimulating, recording, and note-taking. Techniques used to analyze the data were sorting, rechecking, and connecting. Based on the results of this study, it can be concluded that (1) the development of the structure of the word in the development of Indonesian phonological of preschool children with hearing impairment were (a) started from the vocoid (V) structure to a more complex structure (CV, VV, VCV, CVC, CVV, CVCV, CCV, VVC, CCVCV, CVVC, VCCV, VCVVC, CVCVVC); (B) from the word structure ended with vocoid (V) to the structures that ended with contoid (C); (2) the development of phonological syllables in the development of Indonesian preschool children with hearing impairment have the following the sequence of V, CV, VC, CVC, and CCV.